2016
DOI: 10.1016/j.molcel.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Coupling of the Cell Cycle and Circadian Clock in Adult Stem Cell Culture

Abstract: SUMMARY Circadian clock-gated cell division cycles are observed from cyanobacteria to mammals via intracellular molecular connections between these two oscillators. Here we demonstrate WNT-mediated intercellular coupling between the cell cycle and circadian clock in 3D murine intestinal organoids (enteroids). The circadian clock gates a population of cells with heterogeneous cell-cycle times that emerge as 12-hr synchronized cell division cycles. Remarkably, we observe reduced-amplitude oscillations of circadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 49 publications
6
108
0
1
Order By: Relevance
“…The loss of BMAL1 produced no obvious differences in intestinal crypt or villus morphology; however, a slight but significant decline in the number of crypts was noted (Figure 3 A ). This result is consistent with recent findings that the PER1/PER2 double mutant also has a slight decrease in crypt number 28 . The BMAL1 -related difference in baseline crypt number may explain the overall reduction in the number of crypts following irradiation (Figure 2 A ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The loss of BMAL1 produced no obvious differences in intestinal crypt or villus morphology; however, a slight but significant decline in the number of crypts was noted (Figure 3 A ). This result is consistent with recent findings that the PER1/PER2 double mutant also has a slight decrease in crypt number 28 . The BMAL1 -related difference in baseline crypt number may explain the overall reduction in the number of crypts following irradiation (Figure 2 A ).…”
Section: Resultssupporting
confidence: 93%
“…Although these phenotypes seem to be generally compensated during maintenance in vivo (Figure 3) and in vitro (Figure 5 E ), the circadian clock may play a role in epithelial Wnt signaling in certain physiological contexts. While this study was under revision, it was reported that Wnt signaling is regulated by the clock in intestinal organoids, caused by the expression of WNT3A by Paneth cells 28 . Circadian control of intestinal signaling pathways may be an important mechanism linking tissue homeostasis with general physiology.…”
Section: Discussionmentioning
confidence: 86%
“…The cell cycle consists of a series of phases, including DNA replication, various checkpoints and cell division, that allow cell proliferation. Previous studies in cyanobacteria, fungi, plant, zebrafish, and mammals have showed that circadian clocks influence the cell cycle to gate the timing of different phases of DNA synthesis, checkpoints, and cytokinesis (Dekens et al, 2003; Dong et al, 2010; Feillet et al, 2014; Hirayama et al, 2005; Hong et al, 2014; Kowalska et al, 2013; Laranjeiro et al, 2013; Masri et al, 2013; Matsu-Ura et al, 2016; Matsuo et al, 2003; Mori et al, 1996; Nagoshi et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Although the physiological relevance of this finding is still controversial, computational models suggest that the circadian rhythm synchronizes this rhythmic cell cycle entry. [50]…”
Section: Computational Modeling Of Intestinal Organoid Systemsmentioning
confidence: 99%